Ecological impacts of parasitic chytrids, syndiniales and perkinsids on populations of marine photosynthetic dinoflagellates. (February 2016) - Jephcott, Thomas G.; Alves-de-Souza, Catharina; Gleason, Frank H.; van Ogtrop, Floris F.; Sime-Ngando, Télesphore; Karpov, Sergey A.; Guillou, Laure
Abstract: Parasitism is a widespread interaction that plays significant roles in ecosystem balance and evolution. Historically the biology of zoosporic parasites is often a neglected field when studying aquatic ecological dynamics, especially in marine ecosystems. In the marine environment, dinoflagellates represent a significantly large component of primary production, and may be infected by a variety of fungal and fungus-like parasites including chytrids, syndiniales, and perkinsids as well as other microorganisms. The relationship between these organisms and their dinoflagellate hosts constitutes a highly significant pathosystem given the increasing importance of aquaculture. Because of their small size and lack of morphological characteristics these organisms are difficult to identify. This review compares the taxonomy, life cycle, host range, infection strategies, and ecological roles of species of Parvilucifera, Amoebophrya and Dinomyces which are parasites of dinoflagellates. Most of these species have only been described recently. Implications for environmental management are discussed. Graphical abstract: Highlights: Marine dinoflagellates may be infected by a diverse suite of parasitoids. These parasitoids are either true-fungi, or exhibit fungi-like properties. The interactions of these organisms may be viewed as a pathosystem. Human activity can potentially render these pathosystems unstable. Increasing aquacultural activity may be severely affected by marine pathosystems.